Diagnostic Value of Bone Marrow Aspiration and Biopsy in Routine Hematology Practice - Manjit Kaur; Amrit Pal Singh Rana; Shivali Kapoor; Arun Puri (Journal of Clinical and Diagnostic Research, 2014)
Background: The bone marrow is frequently involved in variety of cases presenting with hematological and non-hematological disorders, which are diagnosed by two separate but interrelated techniques such as bone marrow aspiration (BMA) and bone marrow biopsy (BMB). Aim: This study was aimed to assess the diagnostic value of the BMA and BMB and role of both the procedures to reach final diagnosis when done simultaneously. Settings and Design: It was a prospective study. The findings of BMA smears were correlated with BMB sections and data obtained was analysed. Materials and Methods: BMA and BMB were performed on 50 patients. Criteria of inclusion included the main indications for performing this procedure, the availability of full medical records and patient consent. The patients had a male to female sex ratio of 1.6:1 and a wide age range from 4 years to 74 years. Results: In the present study, the main indications for bone marrow examination were categorized. Out of 50 cases studied, in 23 cases, a strong positive correlation between BMA and BMB was noted. However, it was found that in the cases of aplastic anaemia, different phases of myeloproliferative neoplasm (MPN), multiple myeloma, tubercular granulomas and hemato-lymphoid neoplasm, involvement of the marrow was detected better in bone marrow biopsies. Conclusion: The study concludes that preparations of aspirate and trephine biopsy are easy, rapid and complementary to each other in majority of the lesions. The advantage of both the procedures done together enabled us to study the cytomorphology of the cells along with the pattern of distribution of the cells depending on the cases, hence help in making the diagnosis accurately.